Além de Gustavo Barroso : o antissemitismo na ação integralista brasileira (1932-1937) - Vieira, Newton Colombo de Deus (2012)
This research seeks to study the anti Semitism within the Ação Integralista Brasileira, a political movement emerged in Brazil in the 1930s, influenced by european fascism and with considerable accession of militants. The Integralist movement was led by Plinio Salgado, and below it, the chain of command, Gustavo Barroso and Miguel Reale. Gustavo Barroso stood out for leading a radical anti-Semitic current, sometimes conflicting with other movement leaders. The current Barroso had a significant acceptance by some militant fundamentalists, who have published works of extensive anti-Semitic content. In the papers published by the movement, this anti Semitism ends up in the background, however, does not disappear completely.